Osmanlı Diplomasisinde Mihmandar Geleneği - Mustafa CAN (Gazi Akademik Bakış)
The appointment of persons to guide diplomatic guests in which country they are present at is a very old tradition in interstate relations. This tradition, seen in both western and eastern diplomacy, was applied in the Ottoman State within the framework of Ottoman state traditions and diplomacy. For this reason, officials named mihmandar have been appointed in order to deal with official guests from foreign countries. Since it is thought that the mihmandars represent the dignity of Ottoman State in the face of foreign guests, selection of mihmandars has been meticulous. Generally selected from the palace officials, mihmandars were interested in hosting the diplomatic guests coming to the Ottoman lands and their needs as long as they were in the country and providing the coordination between the institutions in this regard. In this context, this practice contains important sections in terms of Ottoman state and diplomacy tradition and has a distinctive feature of the Ottoman State from other contemporary states.